Transmetallation vs adduct: diverse reactivity of N,O-ketiminato germylene with [Cp*MCl2](2) (M = Rh or Ir; Cp* = eta(5)-C5Me5) and MCl5 (M = Nb and Ta) - Raghavendra, Beesam; Bakthavachalam, K.; Das, Tamal; Roisnel, Thierry; Sen, Sakya S.; Vanka, Kumar; Ghosh, Sundargopal (Journal of Organometallic Chemistry, 2020)
The reactions of the germylenes, [(Dipp)NCMeCHCORGeCl] (1a: R = Me, 1b: R = Ph) with [Ir2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] led to the formation of the adducts [(Dipp)NCMeCHCORGeClIrCl2Cp*] (3a: R = Me and 3b: R = Ph). On the other hand, [Rh2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] does not react with the germylenes (1a and 1b). When the reactions of 1a and 1b are carried out with [Cp*TaCl4], the reaction led to decomposition. The reaction of 1a or 1b with TaCl5 yielded the transmetallated products [(Dipp)NCMeCHCORTaCl4] (4a: R = Me, 4b: R = Ph) with the extrusion of GeCl2. Our theoretical studies show that for, the insertion of TaCl5 to 1a and the formation of 4a with concomitant elimination of GeCl2 is energetically favourable. Extrusion of SnCl2 is also observed when the corresponding stannylene, [(Dipp)NCMeCHCOMeSnCl] was reacted with TaCl5. All these compounds have been characterized by H-1 and C-13 NMR spectroscopy, elemental analysis and the constitution of compounds 1b, 3b, and 4a were confirmed by single-crystal X-ray crystallography. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Adduct formation; Germylenes; Iridium; Ketoiminate; Tantalum; Transmetallation